2021
DOI: 10.3390/nu14010174
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Processed Food Consumption and Adult Mortality Risk: A Systematic Review and Dose–Response Meta-Analysis of 207,291 Participants

Abstract: We performed a systematic review and dose–response meta-analysis of observational studies assessing the association between UPF consumption and adult mortality risk. A systematic search was conducted using ISI Web of Science, PubMed/MEDLINE, and Scopus electronic databases from inception to August 2021. Data were extracted from seven cohort studies (totaling 207,291 adults from four countries). Using a random-effects model, hazard ratios (HR) of pooled outcomes were estimated. Our results showed that UPF consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
87
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 45 publications
3
87
1
Order By: Relevance
“…The positive association between consumption of UPF and inflammatory markers that have been seen among women may be explained by the greater accumulation of body fat in women ( 34 ). In line with our study, in 2021, a systematic review and meta-analysis of 7 cohort studies (207,291 adults) showed a significant positive association between UPF consumption and the risk of CVDs among adults with a BMI of more than 25 kg/m 2 ( 35 ). Moreover, a recent narrative review study by Matos et al ( 36 ) concluded that the consumption of UPFs is positively associated with the prevalence of chronic complications, including obesity, hypertension, CVDs, type 2 diabetes, and consequently the risk of all-cause mortality ( 36 ).…”
Section: Discussionsupporting
confidence: 87%
“…The positive association between consumption of UPF and inflammatory markers that have been seen among women may be explained by the greater accumulation of body fat in women ( 34 ). In line with our study, in 2021, a systematic review and meta-analysis of 7 cohort studies (207,291 adults) showed a significant positive association between UPF consumption and the risk of CVDs among adults with a BMI of more than 25 kg/m 2 ( 35 ). Moreover, a recent narrative review study by Matos et al ( 36 ) concluded that the consumption of UPFs is positively associated with the prevalence of chronic complications, including obesity, hypertension, CVDs, type 2 diabetes, and consequently the risk of all-cause mortality ( 36 ).…”
Section: Discussionsupporting
confidence: 87%
“…The effect that ultra-processed food consumption exerts on the carbon and water footprints of the Brazilian diet was then evaluated observing the diet footprints across five strata of the population corresponding to increasing quintiles of the contribution of ultra-processed foods to total energy intake. This was the same approach used by most of the studies evaluating the effect of consumption of ultra-processed foods on diet quality 6 or disease risk [7][8][9] . Crude and adjusted linear regression models and linear trend tests were used to assess the association between quintiles of ultra-processed food dietary contribution and the dietary environmental footprints.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis of findings from national dietary surveys carried out in many countries, including Brazil, shows that increases in the dietary share of ultraprocessed foods are systematically associated with unbalanced dietary nutrient profiles, including higher free sugars and unhealthy fats and lower protein, fiber, and several vitamins and minerals 6 . Systematic reviews and meta-analyses of findings from long-term longitudinal studies, also carried out in many countries, including Brazil, show that increases in the dietary share of ultra-processed foods are associated with higher risk of obesity, diabetes, cardiovascular diseases, depression, and several other chronic non-communicable diseases, in addition to higher all-cause mortality [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, these types of foods are hypothesized to exert detrimental effects on health due to nutritional [ 66 ] and, most importantly, non-nutritional factors, such as chemical additives [ 67 ]. Although several meta-analyses have been published reporting an increased risk of several non-communicable diseases [ 68 , 69 ], research is still ongoing, and the debate whether the benefits would justify the risks is far to be solved. Noteworthy, soy-based meat and dairy alternatives may be implemented in non-Asian countries without requiring modification of meal patterns or food habits by definition, thus resulting in a potential high compliance and ease in reaching population-level targets.…”
Section: Discussionmentioning
confidence: 99%